Age and Defect Size as Predictors of Pulmonary Hypertension in Secundum Atrial Septal Defect: A Retrospective Study from the Himalayan Region - Koirala, Ishita; Panthee, Nirmal; Adhikari, Anu; Timilsina, Pratikshya; Thapa, Awesh; Acharya, Sampada; Pradhan, Sidhartha; Koirala, Raamesh (Nepalese Heart Journal, 2025)
Background and aims: Atrial septal defect is a common congenital heart disease. Most patients are asymptomatic. The incidence and progression of pulmonary hypertension in these defects have important clinical implications. We sought to establish the role of age and defect size as predictors of pulmonary hypertension.Methods: Hospital discharge summaries of patients who underwent surgical defect closure by a single unit of Shahid Gangalal National Heart Center between 2018 and 2023 were retrospectively reviewed. Baseline variables and echocardiography data were analyzed using SPSS. Pulmonary artery systolic pressure of > 50 mmHg in echocardiography was used to define pulmonary hypertension.  A p-value of